Implementation of Image Segmentation Using RGB Color Detection on Virtual Reality Robot as Spy Tool - Rossi Passarella; Sutarno .; Ahmad Rezqy FF (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Humans cannot spy in small places that difficult topass. We need small size robot which remotely controlled so itcan be used for spying. The virtual reality technology in thisresearch was created using image segmentation with RGB colordetection and Pythagoras algorithm. A wireless camera is usedfor replacement of human eye to be able to look at thecircumstances around a robot. The camera can turn to the left orright in accordance with the user's head movement. The webcamis used as a sensor to detect the movement of a human head.Systems were created to be able to detect color and get the anglevalue and work well to move the camera in accordance with theuser's head movement. In this way, the user can act as thoughthey are on the robot and perform the surveillance